2021
DOI: 10.48550/arxiv.2106.14545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-Ray Studies of the Abell 3158 Galaxy Cluster with eROSITA

B. Whelan,
A. Veronica,
F. Pacaud
et al.

Abstract: Context. The most nearby clusters are the best places to study physical and enrichment effects in the faint cluster outskirts. The Abell 3158 cluster (A3158), located at z = 0.059 is quite extended with a characteristic radius r 200 = 23.95 arcmin. The metal distribution in the outskirts of this cluster has previously been studied with XMM-Newton. In 2019, A3158 was observed as a calibration target in a pointed observation with the eROSITA telescope onboard the Spektrum-Roentgen-Gamma (SRG) mission. Bright lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…However, this difference is small, namely of 10-15% in the full 0.7−7 keV band for low-temperature clusters (<4 keV) to which we are sensitive in the eFEDS observations. Our preliminary calibration studies with eROSITA showed that, in general, eROSITA temperatures are in good agreement with Chandra and XMM-Newton temperatures (Sanders et al 2022;Veronica et al 2022;Iljenkarevic et al 2022;Whelan et al 2021). Turner et al (2021) recently cross-matched the eFEDS cluster catalog (Liu et al 2022a) with the XMM-Newton Cluster Survey (XCS, Romer et al 2001) sample and found luminosities of 29 cross-matched clusters to be in excellent agreement.…”
Section: Resultssupporting
confidence: 63%
“…However, this difference is small, namely of 10-15% in the full 0.7−7 keV band for low-temperature clusters (<4 keV) to which we are sensitive in the eFEDS observations. Our preliminary calibration studies with eROSITA showed that, in general, eROSITA temperatures are in good agreement with Chandra and XMM-Newton temperatures (Sanders et al 2022;Veronica et al 2022;Iljenkarevic et al 2022;Whelan et al 2021). Turner et al (2021) recently cross-matched the eFEDS cluster catalog (Liu et al 2022a) with the XMM-Newton Cluster Survey (XCS, Romer et al 2001) sample and found luminosities of 29 cross-matched clusters to be in excellent agreement.…”
Section: Resultssupporting
confidence: 63%
“…Furthermore, if an emission bridge does connect the two clusters, the eRASS image will provide its observation. More generally, given the early eROSITA results on cluster outskirts and infall regions (e.g., Reiprich et al 2021;Ghirardini et al 2021;Churazov et al 2021;Veronica et al 2022;Whelan et al 2021;Sanders et al 2022), and given the close correspondence to similar structures observed in cosmological hydrodynamical simulations (e.g., Biffi et al 2022), we may expect that bridges and clumpy filaments will be discovered in several more nearby systems in the future in the eRASS. These systems can then be studied in detail after the eight surveys are completed using the SRG/eROSITA scanning mode, with which areas of tens of square degrees can be scanned efficiently, homogeneously, and deeply.…”
Section: Discussionmentioning
confidence: 72%
“…Not all the TMs were active during the CalPV observations, as also reported in Table 2. Detailed studies of some interesting astronomical objects in these fields have been published in several papers, including Abell 3391/3395 (Reiprich et al 2021;Veronica et al 2021), Abell 3266 (Sanders et al 2021), Abell 3158 (Whelan et al 2021), Abell 3408 (Iljenkarevic et al 2021), 47 Tuc (Saeedi et al 2021), 1H 0707-495 (Boller et al 2021), high-mass X-ray binaries (HMXBs) in the Small Magellanic Cloud (SMC) (Haberl et al 2021).…”
Section: A3266mentioning
confidence: 99%